Financing Strategy and Financial Management of General Education Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the relationship between strategic financing and financial management in general education schools, addressing a notable knowledge gap in how integrated financial practices impact educational performance. Utilizing a mixed-methods approach, the research combines quantitative budgetary analysis with qualitative case studies to explore both measurable financial outcomes and contextual decision-making dynamics. Findings reveal that schools employing cohesive financial strategies and robust financial management practices achieve superior resource allocation, fiscal accountability, and improved educational outcomes. These results underscore the importance of comprehensive financial frameworks for policymakers and educational administrators, emphasizing the need for strategic financial planning to enhance operational efficiency and educational quality. The study's implications extend to broader educational policy reforms, contributing to the sustainable development of general education systems. However, further research is necessary to explore the long-term impacts of integrated financial strategies, particularly in relation to emerging digital financial tools and evolving public policies, to advance educational finance scholarship.